2004
DOI: 10.1088/0022-3727/37/20/022
|View full text |Cite
|
Sign up to set email alerts
|

Drilling of steel and HgCdTe with the femtosecond pulses produced by a commercial laser system

Abstract: The results of interaction of single and multiple 200 fs laser pulses with thick stainless steel and HgCdTe samples are reported. The threshold laser energy density required to produce surface melting is measured. The melt dynamics and evolution of surface morphology are observed for different pulse energies and number of laser pulses. It is observed that, as with a long laser pulse interaction, a layer of melt can be produced at the sample surface. Melt ejection in the radial direction towards the periphery o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…So those high energy data points are not available for those testing conditions due to the limitations of our equipment. It has been seen that the geometry of the hole can hinder or assist drilling and affect the rate of material removal [1,15]. The difference in drilling speed cannot be accounted for by different absorptivity due to wavelength, so the laser pulse must undergo some significant change in the second harmonic conversion process to explain the reduced drilling rate, or an unaccounted material property makes aluminum more susceptible to drilling at 800 nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…So those high energy data points are not available for those testing conditions due to the limitations of our equipment. It has been seen that the geometry of the hole can hinder or assist drilling and affect the rate of material removal [1,15]. The difference in drilling speed cannot be accounted for by different absorptivity due to wavelength, so the laser pulse must undergo some significant change in the second harmonic conversion process to explain the reduced drilling rate, or an unaccounted material property makes aluminum more susceptible to drilling at 800 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Prior work by two of the authors [1][2][3] has cast doubt on the assumption that modeling ultrashort pulses as Gaussian temporal entities with a few hundred femtoseconds measured at the full width half maximum or 1/e 2 is sufficient. It has also been shown that a low intensity pedestal, which is both difficult to detect and difficult to eliminate, exists below an ultrashort pulse [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The active expansion of the area of practical applications of ultrashort laser pulses motivates experimental and theoretical studies focused on the fundamental mechanisms of laser-materials interactions. Under conditions when laser irradiation results in permanent surface modification or material ejection (ablation), the relevant processes discussed in literature are the transient melting and resolidification of a thin surface layer [8][9][10][11][12], the explosive boiling (phase explosion) of a surface region superheated beyond the limit of thermodynamic stability of the molten material [9,[13][14][15][16][17][18], the melt expulsion or sputtering due to the action of ablation recoil pressure [9,19], the ejection of large droplets or fractured solid fragments caused by the relaxation of photomechanical stresses [9,[20][21][22][23][24][25][26][27], as well as non-thermal phase transformations induced by the electronic excitations [28][29][30][31], photochemical reactions [32] or charge separation and Coulomb explosion [33].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have clearly shown melting and recast effects at fluence levels much greater than the ablation threshold [1]. This observation has led the hypothesis that at high fluence, the pure femtosecond pulse acquires a nanosecond component (pedestal) that represents a significant portion (20% or greater) of the pulse energy (Semak, Thomas, and Campbell, 2004) [11,1].…”
Section: Introductionmentioning
confidence: 99%